Porous metal oxide, preparation method thereof and catalyst
By using the porous metal oxide preparation method, a perovskite catalyst with a highly ordered porous structure and mesoporous structure is formed, which solves the problem of high combustion temperature of soot particles in diesel engine exhaust gas, improves catalytic performance and structural stability, and meets the requirements of relevant regulations.
Patent Information
- Application Number
- CN202411901572.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-04-01
AI Technical Summary
The prior art is difficult to effectively reduce the combustion temperature of soot particles in diesel engine exhaust gas, resulting in low efficiency of catalyst active site utilization and inability to meet the requirements of relevant regulations.
By using the preparation method of porous metal oxides, a perovskite catalyst with a highly ordered porous structure and mesoporous structure is formed using neatly arranged microsphere template agents and block copolymers.
It improves the catalytic performance and structural stability of the catalyst, reduces the combustion temperature of soot, enhances the ability to oxidize NOx and burn soot, and meets the requirements of relevant regulations.
Smart Images

Figure CN119733525A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of porous materials, and in particular to a porous metal oxide and a preparation method and a catalyst thereof. Background Art
[0002] With the development of industrialization and urbanization, diesel engines have been widely used in the fields of mechanical power devices such as automobiles and ships due to their high thermal efficiency, strong reliability and good durability. However, the exhaust emissions of diesel engines have brought serious air pollution problems and major ecological damage. The pollutants emitted by diesel engine exhaust mainly include incompletely burned alkanes, nitrogen monoxide, soot particles and nitrogen oxides. Compared with gasoline engine exhaust, the emissions of incompletely burned alkanes and nitrogen monoxide in diesel engine exhaust are smaller, but the emissions of soot particles and nitrogen oxides are much higher than those of gasoline engines. Since the generation of soot particles and nitrogen oxides is a "one increases while the other decreases", it is difficult to effectively eliminate them by improving engine technology. Therefore, researchers use a combination of pre-treatment technology and post-treatment technology to effectively control the emission of diesel engine pollutants. Pre-treatment technology is currently mainly achieved by improving fuel quality and improving diesel vehicle engine technology. However, due to existing technical limitations, the clean modification of diesel and the improvement of diesel engine body structure cannot completely eliminate carbon soot and cannot meet the requirements of relevant regulations. Therefore, combining external exhaust gas purification technology has become one of the currently recognized effective ways to eliminate diesel engine carbon soot.
[0003] At present, researchers have developed corresponding treatment technologies for different pollutants in diesel exhaust. The current oxidation catalyst-particulate filter-selective catalytic reduction device combined process is a conventional route for diesel exhaust aftertreatment. When using a particulate filter, since the auto-ignition temperature of soot particles (>600℃) is much higher than the working temperature of the particulate filter (200-500℃), in order to avoid the negative impact of the engine performance on the back pressure of the filter caused by soot overload, regeneration technology is essential. The regeneration of particulate filters is divided into active regeneration and passive regeneration. Active regeneration refers to regularly heating the filter to above 550℃ and passing oxygen to oxidize and eliminate the soot particles that clog the filter. Unlike active regeneration, passive regeneration refers to the reaction of soot particles with a suitable catalyst to reduce the combustion temperature of soot particles. At the same time, a small amount of nitrogen dioxide will promote the continuous oxidation of soot particles in the temperature range of 200-450℃. Therefore, the CDPF technology that combines a soot combustion catalyst with a particulate filter has been considered to have broad application prospects.
[0004] Perovskite (ABO3) has been widely studied due to its easily adjustable lattice properties, thermal stability and redox ability. Among them, B-site cation doping can determine the lattice defects, mixed valence states and non-stoichiometric oxygen production of the catalyst. Partial substitution of A-site cations will also affect the oxidation valence state of B-site cations and the overall redox properties of the perovskite phase, thereby affecting the soot combustion activity. The presence of A and B-site ions makes the activity of perovskites easier to control and improve, which is an advantage that other materials hardly have, which gives perovskite catalysts a certain advantage in the field of diesel engine exhaust treatment.
[0005] Therefore, it is necessary to overcome the problem of low utilization efficiency of catalyst active sites caused by gas-solid-solid three-phase reaction, reduce the soot combustion temperature as much as possible, and develop an environmentally friendly, simple and inexpensive preparation method for porous perovskite catalysts, which is becoming increasingly important. Summary of the invention
[0006] In order to solve the above problems, the object of the present invention is to provide a porous metal oxide and a preparation method and catalyst thereof.
[0007] In order to achieve the above object, the present invention provides a method for preparing a porous metal oxide, the preparation method comprising:
[0008] A metal precursor, a block copolymer and a solvent are mixed to obtain a raw material mixed solution, a microsphere template is fully immersed in the raw material mixed solution, and calcined step by step to obtain the porous metal oxide;
[0009] The metal precursor comprises a lanthanum source, a manganese source and an iron source, and the molar ratio of the lanthanum source to the mass of the block copolymer is 10 mmol:0.5-6 g.
[0010] In the above preparation method, the microsphere template is generally a polymer microsphere generated by a polymerization reaction of a monomer initiated by an initiator. The microsphere template thus obtained is generally an orderly arranged microsphere.
[0011] In the preparation method provided by the present invention, neatly arranged microspheres are used as templates, and then a raw material mixture containing a metal precursor and a block copolymer is impregnated into the gaps of the microspheres. The template microspheres are removed through a calcination process. The pore structure of the finally obtained porous perovskite catalyst is highly ordered and has a certain mechanical strength. The pore size in the porous metal oxide can be adjusted by adjusting the size of the microsphere template.
[0012] In the above preparation method, the particle size of the microsphere template is generally 250-400 nm, for example, specific values such as 250 nm, 300 nm, 350 nm, 400 nm, and a range with any two of the above specific values as endpoints.
[0013] In the above preparation method, the microsphere template may specifically include polymethyl methacrylate microspheres.
[0014] According to a specific embodiment of the present invention, the method for preparing the polymethyl methacrylate microspheres may include: mixing methyl methacrylate with an initiator in a protective atmosphere, and performing a polymerization reaction to obtain the polymethyl methacrylate microspheres.
[0015] In the preparation method of polymethyl methacrylate microspheres, the methyl methacrylate used as the raw material can be refined methyl methacrylate. The refining process can be: rotary evaporation of methyl methacrylate, for example, vacuum distillation of methyl methacrylate at 40° C. to remove the polymerization inhibitor contained in methyl methacrylate.
[0016] In the above-mentioned method for preparing polymethyl methacrylate microspheres, the initiator may include potassium persulfate. In some specific embodiments, the mass ratio of the initiator to methyl methacrylate may be controlled to be 0.4-1:100-200.
[0017] In the above-mentioned method for preparing polymethyl methacrylate microspheres, the initiator can also be a refined initiator. The refining process of the initiator can include: dissolving the initiator in water to form an initiator solution (the dissolution temperature can be 50-80°C), cooling and crystallizing with ice water, filtering the crystals and washing them with ice water until there is no sulfate in the washing liquid. The washed crystals are dried under vacuum conditions and sealed for storage. In the above-mentioned refining process, the crystals obtained by crystallization can be white needle-shaped crystals; sulfate can be tested with barium chloride solution, and no precipitation is precipitated after mixing the washing liquid with the barium chloride solution, that is, there is no sulfate; the drying temperature can be 50°C, and the drying time can be 12h; the vacuum drying method can avoid the decomposition of potassium persulfate.
[0018] In the above-mentioned method for preparing polymethyl methacrylate microspheres, the process of mixing methyl methacrylate with an initiator may specifically include: heating the methyl methacrylate solution to a polymerization reaction temperature, heating the initiator to a temperature of methyl methacrylate, and then mixing the methyl methacrylate with the initiator to form a raw material solution for the polymerization reaction.
[0019] In the preparation method of the polymethyl methacrylate microspheres, the particle size of the polymethyl methacrylate microspheres can be controlled by controlling the temperature of the polymerization reaction. Specifically, the temperature of the polymerization reaction can be 75-85°C to form polymethyl methacrylate microspheres with a particle size of about 300nm. In some specific embodiments, the temperature of the polymerization reaction can be 75°C, 76°C, 77°C, 78°C, 79°C, 80°C, 81°C, 82°C, 83°C, 84°C, 85°C and other specific values, as well as a range with any two of the above specific values as endpoints.
[0020] In the above-mentioned method for preparing polymethyl methacrylate microspheres, the polymerization reaction time is 1h-2h, for example, specific values such as 1h, 1.1h, 1.2h, 1.3h, 1.4h, 1.5h, 1.6h, 1.7h, 1.8h, 1.9h, 2h, and a range with any two of the above-mentioned specific values as endpoints.
[0021] In the above-mentioned method for preparing polymethyl methacrylate microspheres, excessive polymerization of monomers can be avoided by carrying out the polymerization reaction in a protective atmosphere. In some specific embodiments, the protective atmosphere can be a nitrogen atmosphere.
[0022] In the preparation method of polymethyl methacrylate microspheres, the polymerization reaction may be accompanied by stirring, the stirring speed may be 300-350 r / min, and the stirring time may be 1.5h-2h, for example, 2h.
[0023] In some specific embodiments, the polymethyl methacrylate microspheres obtained by polymerization may be fluorescent green.
[0024] According to a specific embodiment of the present invention, the method for preparing the polymethyl methacrylate microspheres may further include the operation of post-treating the product of the polymerization reaction. The post-treatment may include filtering, centrifuging and drying the product of the polymerization reaction. Through the filtering and drying process, the microspheres generated by the polymerization may be arranged in an orderly manner. The centrifugal process may be a long-term centrifugation at a low speed to promote the orderly arrangement of the microspheres. Specifically, the speed of the centrifugation may be 3000r / min, and the centrifugation time may be 11-12h.
[0025] In the preparation method of the porous metal oxide, the molar amount of the lanthanum source and the mass ratio of the block copolymer can be controlled to be 10mmol:0.5-6g, for example, 10mmol:0.5g, 10mmol:1g, 10mmol:2g, 10mmol:3g, 10mmol:4g, 10mmol:5g, 10mmol:6g, and other specific values, and ranges with any two of the above specific values as endpoints. Further, the molar amount of the lanthanum source and the mass ratio of the block copolymer can be controlled to be 10mmol:0.5-3g, and further can be controlled to be greater than or equal to 10mmol:0.5g and less than or equal to 10mmol:2g.
[0026] In the above-mentioned method for preparing the porous metal oxide, the molar ratio of the iron source to the lanthanum source is generally controlled to be less than 1: 1. That is, the molar ratio of the iron source to the lanthanum source is greater than 0: 1 and less than or equal to 1: 1, for example, it can be 0.01: 1, 0.05: 1, 0.1: 1, 0.2: 1, 0.3: 1, 0.4: 1, 0.5: 1, 0.6: 1, 0.7: 1, 0.8: 1, 0.9: 1, 1: 1 and other specific values, as well as a range with any two of the above specific values as endpoints.
[0027] In the method for preparing the porous metal oxide, the molar ratio of the manganese source to the lanthanum source is generally controlled to be less than 1: 1. That is, the molar ratio of the manganese source to the lanthanum source is greater than 0: 1 and less than or equal to 1: 1, for example, it can be 0.01: 1, 0.05: 1, 0.1: 1, 0.2: 1, 0.3: 1, 0.4: 1, 0.5: 1, 0.6: 1, 0.7: 1, 0.8: 1, 0.9: 1, 1: 1 and other specific values, as well as a range with any two of the above specific values as endpoints.
[0028] In the method for preparing the porous metal oxide, the lanthanum source may include a lanthanum salt, such as a soluble salt of lanthanum.
[0029] In the method for preparing the porous metal oxide, the iron source may include an iron salt, such as a soluble iron salt.
[0030] In the method for preparing the porous metal oxide, the manganese source may include a manganese salt, such as a soluble manganese salt.
[0031] In the above-mentioned method for preparing porous metal oxide, the anion of the metal precursor may include one or more combinations of acetate, nitrate, and chloride ions. Correspondingly, the lanthanum source may include one or more combinations of lanthanum nitrate, lanthanum acetate, and lanthanum chloride, the manganese source may include one or more combinations of manganese nitrate, manganese acetate, and manganese chloride, and the iron source may include one or more combinations of iron nitrate, iron acetate, and iron chloride. Preferably, the metal precursor may be a nitrate of a metal.
[0032] In the preparation method of the porous metal oxide, the block copolymer can be used as a soft template to promote the generation of mesopores. The porous metal oxide provided by the present invention is a macroporous mesoporous ternary perovskite catalyst, which not only has a three-dimensional ordered macroporous structure, but also has a mesoporous structure, which can provide more contact sites and improve the catalytic performance of the catalyst.
[0033] In some embodiments, the block copolymer may include P123 and / or F127.
[0034] In the above-mentioned method for preparing porous metal oxide, the ratio of the mass of the block copolymer to the molar amount of the lanthanum source is 0.5-6g:10mmol. In some specific embodiments, the amount of the block copolymer can be 0.5g-6g, and further can be greater than or equal to 0.5g and less than 2g. By adjusting the amount of the block copolymer, the catalytic performance of the porous metal oxide can be adjusted.
[0035] In the above-mentioned method for preparing porous metal oxide, the solvent in the raw material mixture generally includes an organic solvent, which is not only used to dissolve the metal precursor, but also can maintain the shape of the microsphere template, which helps to form a macroporous structure. In addition, the organic solvent used in the present invention can avoid the destruction of the macroporous structure during the mesopore formation process. The organic solvent includes ethylene glycol and methanol. When ethylene glycol and methanol are contained at the same time, the volume ratio of the methanol to ethylene glycol can be 1:1-5, for example, specific values such as 1:1, 1:2, 1:3, 1:4, 1:5, and a range with any two of the above specific values as endpoints.
[0036] In the method for preparing the porous metal oxide, the dissolution temperature of the metal precursor in the organic solvent may be 40-50° C. Stirring may be used during the dissolution process to promote uniform dissolution, and the stirring speed may be 400-500 r / min.
[0037] In the above-mentioned method for preparing porous metal oxide, the organic solvent can also dissolve the block copolymer. The organic solvent for dissolving the block copolymer can include methanol and ethylene glycol, such as a combination of methanol and ethylene glycol (the volume ratio can be 1:1-5). The dissolution temperature of the block copolymer in the organic solvent can be 40-50°C. Stirring can be used during the dissolution process to promote uniform dissolution, and the stirring speed can be 400-500r / min.
[0038] According to a specific embodiment of the present invention, the raw material mixture can be obtained by mixing a metal precursor solution formed by dissolving a metal precursor in an organic solvent and a block copolymer solution formed by dissolving a block copolymer in an organic solvent; or it can be obtained by mixing a metal precursor, a block copolymer, and an organic solvent. Among them, the method of mixing the metal precursor solution with the block copolymer solution can prevent the structure of the already polymerized mesoporous precursor template (i.e., the block copolymer) from being destroyed. After the two are mixed, the dissolution temperature (40-50°C) and the rotation speed (400-500r / min) can be maintained for 2 hours.
[0039] In the above-mentioned method for preparing porous metal oxide, the mass ratio of lanthanum source to microsphere template in the raw material mixture can be 1:1-5, for example, specific values such as 1:1, 1:2, 1:3, 1:4, 1:5, and ranges with any two of the above specific values as endpoints. In some specific embodiments, the specific amount of microsphere template can be 4-6g.
[0040] In the above-mentioned method for preparing porous metal oxide, after the microsphere template is mixed with the raw material mixture, bubbles are observed on the surface of the microsphere template, indicating that the raw material mixture begins to enter the interior of the microsphere template, and this time can be regarded as the start time of impregnation.
[0041] In the above-mentioned method for preparing porous metal oxide, the immersion time can be controlled to be more than 12 hours, for example, 24 hours, and the immersion temperature can be room temperature, specifically 25° C.-30° C.
[0042] In the above-mentioned method for preparing porous metal oxide, the impregnation process can be carried out under vacuum conditions to promote the penetration of the raw material mixture into the interior of the microsphere template.
[0043] In the above-mentioned method for preparing porous metal oxide, the method may further include filtering and drying the impregnated microsphere template, and then calcining in steps. The drying temperature may be 60° C., and the drying time may be 24-48 hours.
[0044] In the above-mentioned method for preparing porous metal oxide, through the process of step-by-step calcination, the metal precursor generates metal oxide, and the metal oxide anti-topological microsphere template is arranged to form an ordered structure. The microsphere template is removed to obtain a macroporous structure with an ordered arrangement. Existing methods for removing the template include chemical removal and one-step calcination removal: the chemical removal method cannot completely remove the template, and the conventional one-step calcination method can completely remove the template, but it will cause the porous structure formed by the metal oxide to deteriorate or even be destroyed. The present invention can completely remove the template on the basis of protecting the ordered macroporous structure of the metal oxide from being destroyed by calcining in steps and controlling the calcination temperature.
[0045] In the above-mentioned method for preparing the porous metal oxide, the step-by-step calcination may include a first calcination and a second calcination. The porous metal oxide provided by the present invention contains manganese. Although manganese has a higher NO-TPO activity than other metal elements, the thermal stability of manganese is relatively low. If a one-step calcination method is used, the three-dimensional ordered macroporous structure will collapse. The present invention separates the process of removing the template from the product formation process by step-by-step calcination. First, a lower calcination temperature (first calcination) is used to remove the microsphere template to form macropores and simultaneously form mesopores, and then a higher calcination temperature (second calcination) is used to promote the formation of a porous perovskite catalyst.
[0046] In the above-mentioned method for preparing porous metal oxide, by controlling the temperature of the first calcination, the template agent can be completely removed, mesopores can be formed, and the porous structure can be protected from damage. The lanthanum source and the manganese source can be calcined under air to form Fe-doped LaMnO3 perovskite catalyst. By adjusting the ratio of manganese element and iron element, lanthanum manganate perovskite catalyst doped with different contents of iron can be obtained.
[0047] In the above-mentioned method for preparing porous metal oxide, the temperature of the first calcination can be controlled to be 300-400°C, for example, 300°C, 310°C, 320°C, 330°C, 340°C, 350°C, 360°C, 370°C, 380°C, 390°C, 400°C and other specific values, and a range with any two of the above specific values as endpoints; the time of the first calcination can be controlled to be 2-4h, so that there is sufficient time to form macropores and mesopores, for example, 2h, 2.5h, 3.h, 3.5h, 4h and other specific values, and a range with any two of the above specific values as endpoints. In some specific embodiments, the process of the first calcination also includes heating from room temperature (about 30°C) to the temperature of the first calcination, and the heating rate can be controlled to be 1°C / min.
[0048] In the method for preparing the porous metal oxide, the temperature of the second calcination can be controlled to be 550-700°C, such as 550°C, 600°C, 650°C, 700°C and other specific values, and a range with any two of the above specific values as endpoints; the time of the second calcination is 2h-4h, such as 2h, 2.5h, 3.h, 3.5h, 4h and other specific values, and a range with any two of the above specific values as endpoints. In some specific embodiments, the second calcination process also includes heating from the temperature of the first calcination to the temperature of the second calcination, and the heating rate can be controlled to be 1°C / min.
[0049] In the above-mentioned method for preparing the porous metal oxide, the first calcination and the second calcination process may be carried out by placing the microsphere template completely impregnated with the metal salt into a tube furnace, and the calcination atmosphere may be an air atmosphere.
[0050] According to a specific embodiment of the present invention, the method for preparing the porous metal oxide may specifically include:
[0051] 1. In a protective atmosphere, an initiator (preferably refined) and methyl methacrylate (preferably refined) are mixed, and a polymerization reaction is carried out at 75-85° C. for 1 h-2 h; the product of the polymerization reaction is filtered, centrifuged, and dried to obtain the polymethyl methacrylate microspheres; the polymethyl methacrylate microspheres have an orderly arrangement and can be used as a microsphere template;
[0052] 2. Mix the metal precursor, block copolymer and organic solvent to form a raw material mixed solution, fully immerse the microsphere template agent in the raw material mixed solution, filter and dry, put the fully impregnated methyl methacrylate microspheres (generally in the form of fragments) into a tube furnace, heat to 300-400° C. in an air atmosphere for a first calcination for 2h-4h, and then heat to 550-700° C. for a second calcination for 2h-4h to obtain the porous metal oxide. The porous metal oxide has a mesoporous and macroporous structure.
[0053] The present invention also provides a porous metal oxide obtained by the above preparation method. The porous metal oxide can be iron-doped lanthanum manganate perovskite, which can be used as a perovskite catalyst.
[0054] The porous metal oxide provided by the present invention belongs to a perovskite catalyst, has high structural stability, and has a porous structure. The porous metal oxide has macropores and mesopores, and has dispersed mesopores on the pore walls of the macropores.
[0055] In some specific embodiments, the pore size of the macropores in the porous metal oxide is 200nm-300nm, for example, 200nm, 210nm, 220nm, 230nm, 240nm, 250nm, 260nm, 270nm, 280nm, 290nm, 300nm and other specific values, as well as a range with any two of the above specific values as endpoints.
[0056] In some specific embodiments, the pore size of the mesopores in the porous metal oxide is 2nm-50nm, for example, 2nm, 3nm, 4nm, 5nm, 6nm, 7nm, 8nm, 9nm, 10nm and other specific values and ranges with any two of the above specific values as endpoints. Further, the pore size of the mesopores of the porous metal oxide can be 2nm-10nm.
[0057] In the above-mentioned porous metal oxide, the porous metal oxide comprises a skeleton structure, and the voids in the skeleton are macropores, uniformly distributed and periodically arranged, forming a three-dimensional ordered macroporous structure. Adding a block copolymer during the preparation process of the porous metal oxide will not significantly change the three-dimensional ordered macroporous structure of the porous metal oxide, but can additionally form mesopores on the walls of the macropores.
[0058] In the above porous metal oxide, the pore wall thickness of the porous metal oxide can be 25nm-40nm. The porous metal oxide has uniform pore size, window size and wall thickness, and the macropores are highly periodically arranged and connected by pore windows; the mesoporous structure is formed by block copolymers polymerized together, so the mesoporous structure is polymerized on the pore wall.
[0059] In the above-mentioned porous metal oxide, the porous metal oxide contains lanthanum, iron and manganese. Among them, lanthanum can provide a supporting structure for the formation of perovskite catalysts, and iron and manganese are metal active components with variable oxidation states and the ability to generate oxygen vacancies. By doping iron in lanthanum-manganese-based materials, the catalytic activity can be improved, so that the catalyst has a higher oxygen storage capacity and excellent redox performance, which can be widely used in NO x Oxidation and soot combustion. The mesopores in the porous metal oxides can provide more contact area between the reactants and the catalyst, further improving the catalytic activity of the porous metal oxides.
[0060] The present invention also provides a catalyst, which includes the above-mentioned porous metal oxide, or is made of the above-mentioned porous metal oxide. The porous metal oxide provided by the present invention has an orderly arranged macroporous structure and mesoporous structure, so that the catalyst material has a high specific surface area and can expose more active sites; and the elements in the porous metal oxide are evenly distributed, the active sites are dispersed, and the morphology is uniform. Therefore, the porous metal oxide has a high catalytic activity when applied to a catalyst (for example, in the direction of purifying exhaust gas).
[0061] According to a specific embodiment of the present invention, the catalyst may be a soot oxidation catalyst and / or a NO x Oxidation catalysts, that is, the porous metal oxides can be used in the catalytic oxidation of soot and NO x Catalytic oxidation process.
[0062] According to a specific embodiment of the present invention, in terms of physical spatial structure, the above-mentioned preparation method provided by the present invention designs a catalyst morphology having good compatibility with soot particles, and uses the macroporous structure or open space of the catalyst itself to capture soot particles, so that the soot particles can be dispersed on the outer surface of the catalyst. Specifically, the present invention can increase the contact area between soot and the catalyst by designing a three-dimensional ordered macroporous (3DOM) catalyst; at the same time, the catalyst with a three-dimensional ordered macroporous structure is modified by F127 or P123 to obtain a three-dimensional ordered macroporous catalyst with a mesoporous structure, and the mesoporous structure on the three-dimensional ordered macroporous skeleton can promote the dissociation and diffusion of gas-phase oxides to a certain extent.
[0063] The beneficial effects of the present invention include: the porous metal oxide provided by the present invention has an orderly arranged macroporous structure, and has structurally stable pore windows, metal elements are evenly distributed, and has the characteristics of large surface area, uniform element distribution, high activity, high purity, no agglomeration, good stability, etc., and can be applied to diesel engine exhaust treatment; by further adding block copolymers during the preparation process of the oxide, a mesoporous structure can be introduced into the material, so that the catalytic performance of the porous metal oxide is further improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0064] Figure 1 1 and 2 are X-ray diffraction patterns of the macroporous perovskite catalysts of Comparative Examples 1 to 4.
[0065] Figure 2 , Figure 3 , Figure 4 , Figure 5 They are scanning electron microscope images of the catalysts of Comparative Example 1, Comparative Example 2, Comparative Example 3, and Comparative Example 4, respectively.
[0066] Figure 6 This is the energy dispersive X-ray spectroscopy elemental spectrum of the catalyst of Comparative Example 2.
[0067] Figure 7 , Figure 8 , Fig. 9 They are scanning electron microscope images of the catalysts of Comparative Example 5, Comparative Example 6, and Comparative Example 7, respectively.
[0068] Fig.10 , Fig.11 They are scanning electron microscope images of the catalysts of Comparative Examples 8 and 9 respectively.
[0069] Fig.12 This is a temperature-programmed test diagram of the low-temperature catalytic oxidation of NO by the catalysts of Comparative Examples 1 to 4.
[0070] Fig.13 These are test diagrams of soot combustion catalytic oxidation of the catalysts of Comparative Examples 1 to 4 and pure soot (without porous perovskite catalyst).
[0071] Fig.14 This is a test diagram of the catalytic oxidation of soot combustion of the catalyst of Comparative Example 2 under different NO concentration conditions.
[0072] Fig.15 This is a transmission electron microscopy image of the macroporous mesoporous Fe-doped LaMnO3 perovskite catalyst of Example 2.
[0073] Fig.16 The nitrogen adsorption and desorption isotherms of the catalysts of Comparative Example 2 and Example 2 are shown.
[0074] Fig.17 , Fig.18 , Fig.19 , Fig. 20 The scanning electron microscope images of the macroporous and mesoporous Fe-doped LaMnO3 perovskite catalysts of Example 1, Example 2, Example 3, and Example 4 are respectively.
[0075] Fig.21 This is a scanning electron microscope energy spectrum of the catalyst of Example 2.
[0076] Fig. 22 , Fig.23 , Fig.24 The scanning electron microscope images of the macroporous and mesoporous Fe-doped LaMnO3 perovskite catalysts of Example 5, Example 6 and Example 7 are shown respectively.
[0077] Fig.25 This is a temperature-programmed test diagram of low-temperature catalytic oxidation of NO by the porous perovskite catalysts of Example 1, Example 2, Example 5, Example 6 and Comparative Example 2.
[0078] Fig.26These are test diagrams of carbon soot combustion catalytic oxidation of the porous perovskite catalysts of Example 1, Example 2, Example 5, Example 6 and Comparative Example 2.
[0079] Fig. 27 The NO oxidation catalytic stability test results of the catalysts of Comparative Example 2 and Example 2 are shown.
[0080] Fig.28 , Fig.29 The soot combustion cycle stability test results of the catalysts of Comparative Example 2 and Example 2 are shown respectively.
[0081] Fig.30 This is the SEM image of the microsphere template prepared in Comparative Example 1. DETAILED DESCRIPTION
[0082] In order to have a clearer understanding of the technical features, purposes and beneficial effects of the present invention, the technical solution of the present invention is now described in detail below, but it should not be construed as limiting the applicable scope of the present invention.
[0083] Comparative Example 1: This experiment provides a method for preparing a macroporous perovskite catalyst, comprising the following steps:
[0084] 1. Pour 120 ml of refined methyl methacrylate into a 3000 ml four-necked bottle, then add 450 ml of deionized water to form a methyl methacrylate solution, introduce nitrogen and turn on the condensation device;
[0085] The potassium persulfate was heated and dissolved, and the temperature was raised to 80° C. at a speed of 400 r / min while being stirred uniformly. After the solution in the four-necked bottle was heated to 80° C., the 80° C. potassium persulfate solution (containing 0.6 g of potassium persulfate) was added to the four-necked bottle containing the methyl methacrylate solution to carry out polymerization reaction, and stirred for 2 hours;
[0086] The product of the polymerization reaction was filtered, and the obtained filtrate was placed in a 50 ml large centrifuge tube and centrifuged at a speed of 3000 r / min for 11-12 hours. After drying for 24 hours, orderly arranged polymethyl methacrylate microspheres were obtained, which were microsphere template agents. The microsphere template agent was fluorescent green.
[0087] 2. Put 4.3301 g of lanthanum nitrate hexahydrate and 3.579 g of 50% manganese nitrate aqueous solution into a 100 ml beaker, then pour in 50 ml of methanol and ethylene glycol in a volume ratio of 1:4, turn on the stirring setting to 400 r / min and heat to 40°C, heat and stir until the metal salt is completely dissolved to obtain a metal precursor solution (i.e., without adding an iron source);
[0088] 3. Add 6 grams of the dried microsphere template to the above metal precursor solution and vacuum impregnate for 24 hours. Filter the impregnated fragmented microsphere template and dry it for 24 hours. Put the fragmented microspheres completely impregnated with metal salts into a tubular furnace for air calcination; first heat to 300°C and keep it for 3 hours for the first calcination, and then heat to 650°C and keep it for 4 hours for the second calcination to obtain macroporous lanthanum manganate perovskite, which can be used as a three-dimensional ordered macroporous perovskite catalyst.
[0089] Comparative Example 2: This experiment provides a method for preparing a macroporous perovskite catalyst, which is similar to the method in Comparative Example 1, except that the amount of 50% manganese nitrate solution in this experiment is 3.2211 g, and the amount of ferric nitrate nonahydrate is increased to 0.404 g. The catalyst is Fe-doped LaMnO3 perovskite.
[0090] Comparative Example 3: This experiment provides a method for preparing a macroporous perovskite catalyst, which is similar to the method in Comparative Example 1, except that the amount of 50% manganese nitrate solution in this experiment is 2.8632 g, and the amount of ferric nitrate nonahydrate is increased to 0.808 g. The catalyst is Fe-doped LaMnO3 perovskite.
[0091] Comparative Example 4: This experiment provides a method for preparing a macroporous perovskite catalyst, which is similar to the method in Comparative Example 1, except that in this experiment, no 50% manganese nitrate solution is added (i.e., no manganese source is added), and the amount of ferric nitrate nonahydrate is increased to 4.04 g. The catalyst is lanthanum ferrite perovskite.
[0092] The main experimental parameters of Comparative Examples 1 to 4 are summarized in Table 1.
[0093] Table 1
[0094]
[0095] Figure 1 The X-ray diffraction (XRD) of the catalysts of Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4. It can be seen from XRD that the diffraction peaks of the catalysts of Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4 correspond one to one with the corresponding standard cards, and the diffraction peaks have narrow and sharp peak shapes, which are consistent with the basic peak shape of perovskite, indicating that the perovskite structure has been formed.
[0096] Furthermore, through the results of X-ray diffraction experiments (XRD), the catalysts of Comparative Examples 1, 2, 3 and 4 correspond to the standard cards of LaFeO3 and LaMnO3, and the diffraction peaks appearing on XRD are mostly narrow and sharp, which is consistent with the general characteristics of perovskite diffraction peaks. Figure 1It can be seen that the catalyst of Comparative Example 1 is a lanthanum manganate perovskite catalyst; the diffraction peaks of the catalysts of Comparative Examples 2 and 3 shift to the left as the Fe content increases. This is because although the radius of iron is smaller than that of manganese ions, the radii of iron ions and manganese ions are very small and cannot resist the compressive stress that causes crystal deformation. Therefore, the catalysts of Comparative Examples 2 and 3 are Fe-doped LaMnO3 perovskite catalysts; the catalyst of Comparative Example 4 is a lanthanum ferrite perovskite catalyst. Through XRD, it can be proved that the Fe-doped LaMnO3 perovskite catalyst can be successfully synthesized when the iron source, lanthanum source and manganese source are added at the same time.
[0097] Figures 2 to 5 The scanning electron microscope images of the porous perovskite catalysts of Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4 are shown respectively. Figure 2 Figure 5 It can be seen that the porous perovskite catalyst prepared in the above experiment has macropores with an average pore size of about 260nm, which is smaller than the diameter of the methyl methacrylate microspheres used as the template (300nm). The pore size of the above macroporous perovskite catalyst is smaller than the diameter of the template microspheres due to the fact that during the calcination process of the catalyst, the high temperature causes the microsphere template to shrink slightly in its overall structure. In the macroporous perovskite catalyst, the highly ordered macropores are periodically connected to each other through the tight pore walls, and almost no agglomerated particles are observed on the surface.
[0098] Compare with the above Figures 2 to 5 The morphology results of the macroporous perovskite catalysts are shown in Figure 1, wherein the catalysts of Comparative Example 1, Comparative Example 2, Comparative Example 3, and Comparative Example 4 contain macropores with uniform size and regular morphology.
[0099] Figure 6 This is an energy dispersive X-ray spectroscopy (EDS) elemental spectrum photo of the macroporous perovskite catalyst prepared in Comparative Example 2. Figure 6 It can be seen that in the macroporous perovskite catalyst, the three elements of lanthanum, iron and manganese are evenly distributed on the surface of the macroporous structure.
[0100] Fig.30 This is a SEM image of the microsphere template prepared in Comparative Example 1. It can be seen that the particle size of the microsphere template prepared in the present invention is about 300 nm, and the microspheres are arranged in an orderly manner.
[0101] The macroporous structure of the above-mentioned macroporous perovskite catalyst is suitable for gas-solid reactions, and the large pore size of about 260 nm makes it easy for pollutants to enter the inner pores and fully contact with the catalyst.
[0102] Comparative Example 5: This experiment provides a method for preparing a macroporous perovskite catalyst, see Table 2. The preparation method is similar to the method in Comparative Example 2, except that the calcination temperature in the second stage of this experiment is 450°C, and the catalyst is Fe-doped LaMnO3 perovskite.
[0103] Comparative Example 6: This experiment provides a method for preparing a macroporous perovskite catalyst, see Table 2. The preparation method is similar to the method in Comparative Example 2, except that the calcination temperature in the second stage of this experiment is 550°C, and the catalyst is Fe-doped LaMnO3 perovskite.
[0104] Comparative Example 7: This experiment provides a method for preparing a macroporous perovskite catalyst, see Table 2. The preparation method is similar to the method in Comparative Example 2, except that the calcination temperature in the second stage of this experiment is 750°C, and the catalyst is Fe-doped LaMnO3 perovskite.
[0105] Table 2
[0106]
[0107] Figures 7 to 9 The scanning electron microscope images of the macroporous perovskite catalysts of Comparative Example 5, Comparative Example 6 and Comparative Example 7 are shown respectively. Figures 7 to 9 It can be seen that different second calcination temperatures have a close influence on the formation of the pore structure of the catalyst. Compared with Comparative Example 2, due to the low second calcination temperature, the pore structure of Comparative Example 5 is not obvious, the microsphere template shrinks less, and the pore wall is thicker; the pore structure of Comparative Example 6 is relatively complete and the pore wall is thinner, but it can still be observed in the subtle places that some microsphere templates have only melted and shrunk, and no pore structure has been formed; and due to the high calcination temperature of Comparative Example 7, the macropore wall is too thin, and the pore structure is obviously destroyed. Therefore, when the second calcination temperature is 550-700°C, the macropore structure of the Fe-doped LaMnO3 perovskite catalyst obtained is better, and its specific surface area can be further increased to promote the reaction.
[0108] Comparative Example 8: This experiment provides a method for preparing a perovskite catalyst, see Table 3, the preparation method is similar to the method in Comparative Example 2, the only difference is that the solvent in this experiment uses the same amount of anhydrous ethanol to replace the methanol and ethylene glycol in Comparative Example 2. The catalyst obtained in this experiment is iron-doped lanthanum manganate.
[0109] Comparative Example 9: This experiment provides a method for preparing a perovskite catalyst, see Table 3, the preparation method is similar to the method in Comparative Example 2, the only difference is that the solvent in this experiment uses the same amount of ethylene glycol to replace the methanol and ethylene glycol in Comparative Example 2. The catalyst obtained in this experiment is iron-doped lanthanum manganate.
[0110] Table 3
[0111]
[0112]
[0113] Fig.10 and Fig.11 The following are scanning electron microscope images of the catalysts prepared in Comparative Example 8 using anhydrous ethanol alone and Comparative Example 9 using ethylene glycol alone as the organic solvent. Fig.10 and Fig.11 It can be seen that in the early stage of preparation, anhydrous ethanol causes the catalyst to form a gel and the catalyst agglomerates, so it is impossible to form a macroporous structure. Ethylene glycol is too viscous, resulting in too thick pore walls in the macroporous structure, and the macroporous structure is not formed obviously, which is not conducive to the gas phase mass transfer process.
[0114] Test Example 1: This test example provides the catalytic performance test results of the macroporous perovskite catalyst prepared in the above comparative example. Fig.12 and Fig.13 .
[0115] (1) NO catalytic oxidation test. The catalytic performance of the porous perovskite catalyst for NO oxidation reaction was evaluated under a gradient temperature increase of 5 vol% O2 and 500 ppm NO. The evaluation method is as follows: the catalyst activity was tested in a fixed bed reactor with a diameter of 30 mm and a length of 500 mm. Weigh 0.1 g of the sample and put it into a quartz tube. Inject 40 mL / min of nitrogen into the infrared chromatographic gas cell in front of the reaction to eliminate other gases inside. After sweeping the background, inject 5 mL / min of nitric oxide as a pollutant and 5 vol% of oxygen, with a total gas flow of 50 mL / min; heat from 50°C to 100°C at a heating rate of 10°C / min, and then heat to 500°C at 2°C / min.
[0116] In practical applications, the catalytic activity of the catalyst in the low temperature zone is more valuable than that in the high temperature zone. Therefore, the following mainly compares the catalytic activity of the perovskites in Comparative Example 1, Comparative Example 2, Comparative Example 3, and Comparative Example 4 in the low temperature zone: Fig.12 This is a temperature-programmed test diagram of the low-temperature catalytic oxidation of NO by the above perovskite sample. Fig.12 It can be seen that at 250°C, the order of NO conversion activity of each sample is: Comparative Example 2>Comparative Example 1>Comparative Example 3>Comparative Example 4. In addition, in the test range of 100-500°C, the highest NO x The temperature corresponding to the conversion rate is 325°C, and the highest NO x The temperature corresponding to the conversion rate is 318°C, and the highest NO xThe temperature corresponding to the conversion rate is 337°C, and the highest NO x The temperature corresponding to the conversion rate is 372°C.
[0117] (2) Soot combustion catalytic oxidation test. The catalytic performance of the porous perovskite catalyst for the catalytic oxidation reaction of soot combustion was evaluated under a gradient temperature increase of 5 vol% O2 and 2000 ppm NO. The evaluation method is as follows: the catalyst activity was tested in a fixed bed reactor with a diameter of 30 mm and a length of 500 mm. Weigh 0.1 g of perovskite sample and 0.01 g of soot (at a mass ratio of 10:1), grind them thoroughly in a loose contact manner and put them into a quartz tube. A mixed gas containing 20 mL / min (2000 ppm) of nitric oxide, 5 mL / min of oxygen and 25 mL / min of nitrogen was injected into the gas channel, sampled once every 5 minutes, and the components were analyzed by gas chromatography; heated from 30°C to 150°C at a heating rate of 10°C / min, and then heated to 600°C at 2°C / min. Among them, in order to compare the catalytic performance of the catalyst, an additional soot combustion catalytic oxidation control sample without catalyst was added, denoted as SOOT. The results of the soot combustion catalytic oxidation test are summarized in Fig.13 and Table 4.
[0118] Table 4
[0119] Experiment No. <![CDATA[T 10 (℃)]]> <![CDATA[T 50 (℃)]]> <![CDATA[T 90 (℃)]]> Comparative Example 1 328.4 402.6 452.3 Comparative Example 2 320.9 397.0 443.5 Comparative Example 3 339.0 422.4 472.4 Comparative Example 4 373.7 446.4 489.8 SOOT 416.0 580.0 666.0
[0120] T 10 , T 50 and T 90 It refers to the temperature required for the soot conversion rate to reach 10%, 50% and 90% respectively. The lower the temperature, the higher the catalytic activity. 50 is the most important measurement value. From Table 4 and Fig.12 It can be seen that the soot conversion activity (T 50 The order of the macroporous catalysts is: Comparative Example 2 > Comparative Example 1 > Comparative Example 3 > Comparative Example 4, which is basically consistent with the results of NO catalytic oxidation activity. Among all the macroporous catalysts, the T of the sample of Comparative Example 2, which showed the best activity, 10 , T 50 , T 90 The catalytic oxidation activity of all catalysts can improve the reaction rate of soot combustion. The best activity of the comparative example 2 sample can 50 Increased by 183℃.
[0121] At the same time, in order to study the effect of NO on the soot combustion reaction, the soot combustion reaction effect of the catalyst of comparative example 2 at NO concentrations of 0ppm, 500ppm, 1000ppm, and 2000ppm was tested respectively. The results are shown in Fig.14 .like Fig.14 As shown in the figure, for Comparative Example 2, after adding 500ppm NO, the T 50 However, with the further increase of NO, the T of the soot combustion reaction increased to 1000ppm and 2000ppm NO. 50 The decrease tends to be slow, which shows that the improvement of NO on the soot combustion reaction is limited.
[0122] Example 1: This example provides a method for preparing a macroporous mesoporous ternary perovskite catalyst, comprising:
[0123] 1. Pour 120 ml of refined methyl methacrylate into a 3000 ml four-necked bottle, then add 450 ml of deionized water, introduce nitrogen and turn on the condensation device;
[0124] The potassium persulfate was heated and dissolved, and the temperature was raised to 80° C. at a speed of 300 r / min while being stirred uniformly. After the solution in the four-necked bottle was heated to 80° C., the 80° C. potassium persulfate solution (containing 0.6 g of potassium persulfate) was added to the four-necked bottle containing the methyl methacrylate solution to carry out polymerization reaction, and stirred for 2 hours;
[0125] The product of the polymerization reaction was filtered, and the filtrate obtained after filtration was placed in a 50 ml large centrifuge tube and centrifuged at a speed of 3000 r / min for 11-12 hours, and then dried for 24 hours to obtain an orderly arranged microsphere template agent. The microsphere template exhibits fluorescent green.
[0126] 2. Put 4.3301 g of lanthanum nitrate hexahydrate, 3.2211 g of 50% manganese nitrate aqueous solution and 0.404 g of ferric nitrate nonahydrate into a 100 ml beaker, and then pour in 20 ml of methanol and ethylene glycol in a volume ratio of 1:4, turn on the stirring setting to 400 r / min, heat to 40°C, and stir until the metal salt is completely dissolved to obtain a metal precursor solution; put 0.5 g of F127 in a 100 ml beaker, and then pour in 20 ml of methanol and ethylene glycol in a volume ratio of 1:4, turn on the stirring setting to 400 r / min, heat to 40°C, and stir until F127 is completely dissolved to obtain an F127 solution; add the metal salt solution dropwise into the F127 solution, and stir at a constant temperature for 2 hours to obtain a raw material mixture.
[0127] Add 6 grams of dried microsphere template into the above raw material mixture and vacuum impregnate for 24 hours. Filter the impregnated fragmented microsphere template and dry it for 24 hours. Put the fragmented microspheres completely impregnated with metal salt into a tubular furnace for calcination in air. First, heat it to 300°C at a heating rate of 1°C / min and keep it for 3 hours for the first calcination. Then, heat it to 650°C at a heating rate of 1°C / min and keep it for 4 hours for the second calcination to obtain a macroporous mesoporous Fe-doped LaMnO3 perovskite catalyst.
[0128] Example 2: This example provides a method for preparing a macroporous mesoporous ternary perovskite catalyst. The preparation method is similar to the method in Example 1, with the only difference being that the amount of F127 in this example is changed to 1 gram to obtain a macroporous mesoporous Fe-doped LaMnO3 perovskite catalyst.
[0129] Example 3: This example provides a method for preparing a macroporous mesoporous ternary perovskite catalyst. The preparation method is similar to the method in Example 1, with the only difference being that the amount of F127 in this example is changed to 2 grams to obtain a macroporous mesoporous Fe-doped LaMnO3 perovskite catalyst.
[0130] Example 4: This example provides a method for preparing a macroporous mesoporous ternary perovskite catalyst. The preparation method is similar to the method in Example 1, with the only difference being that the amount of F127 in this example is changed to 3 grams to obtain a macroporous mesoporous Fe-doped LaMnO3 perovskite catalyst.
[0131] The main experimental parameters of the above-mentioned Examples 1, 2, 3 and 4 are summarized in Table 5.
[0132] Table 5
[0133]
[0134] In order to prove the formation of mesopores, TEM method was used to observe the mesopores. Fig.15 is a transmission electron microscope image of the catalyst of Example 2, from Fig.15 It can be seen that the macropores in the catalyst are still around 260nm, and the introduction of mesopores will not change the size of the macropores. At the same time, it can be seen that there are disorderly distributed mesopores on the pore wall, and the size of the mesopores is around 5nm. Fig.16The BET nitrogen adsorption and desorption isotherms of the catalysts of Example 2 and Comparative Example 2 clearly show that the BET adsorption and desorption diagrams show a type II isotherm, which can reflect the physical adsorption process of the macroporous structure. In contrast, between the relative pressure of 0.3-0.4, the hysteresis loop of the catalyst of Example 2 shows a typical H4-type hysteresis loop, indicating the formation of a mesoporous structure. The total pore volume of the catalyst of Example 2 was measured to be 0.8332 ml / g, and the total pore volume of Comparative Example 2 was 0.0888 ml / g. It can be seen that the pore structure of Example 2 is more developed than that of Comparative Example 2.
[0135] Figures 17 to 20 The scanning electron microscope images of the catalysts of Example 1, Example 2, Example 3 and Example 4 show that when the amount of F127 added is 0.5g and 1g, the three-dimensional ordered macroporous structure is almost not damaged, while when the amount of F127 added is increased to 2g and 3g, the three-dimensional ordered macroporous structure is partially damaged, resulting in a certain degree of decrease in the catalytic performance of the catalyst.
[0136] Fig.21 This is a scanning electron microscope spectrum of the catalyst of Example 2. It can be seen that in the macroporous mesoporous ternary perovskite catalyst provided by the present invention, the three elements of La, Mn and Fe are uniformly dispersed on the surface of the macroporous structure.
[0137] Example 5: This example provides a method for preparing a macroporous mesoporous ternary perovskite catalyst. The preparation method is similar to the method in Example 1, with the only difference being that F127 in this example is replaced with P123, and its dosage is 0.5 g to obtain a macroporous mesoporous Fe-doped LaMnO3 perovskite catalyst.
[0138] Example 6: This example provides a method for preparing a macroporous mesoporous ternary perovskite catalyst. The preparation method is similar to the method in Example 1, with the only difference being that F127 in this example is replaced with P123, and its dosage is 1 gram to obtain a macroporous mesoporous Fe-doped LaMnO3 perovskite catalyst.
[0139] Example 7: This example provides a method for preparing a macroporous mesoporous ternary perovskite catalyst. The preparation method is similar to the method in Example 1, with the only difference being that F127 in this example is replaced with P123, and its dosage is 2 grams to obtain a macroporous mesoporous Fe-doped LaMnO3 perovskite catalyst.
[0140] The main experimental parameters of the above-mentioned Examples 5, 6 and 7 are summarized in Table 6.
[0141] Table 6
[0142]
[0143] Figure 22 to Figure 24 These are scanning electron microscope images of Example 5, Example 6 and Example 7. Similarly, when the amount of P123 added is small, when the mass of P123 is 0.5g and 1g, the three-dimensional ordered macroporous structure is almost not damaged, but when the amount of P123 added is increased to 2g, the three-dimensional ordered macroporous structure is damaged to a certain extent, causing the catalytic performance of the catalyst to decline to a certain extent.
[0144] The macroporous mesoporous structure of the macroporous mesoporous ternary perovskite catalyst is suitable for gas-solid reaction. The large pore size of about 260nm makes it easy for pollutants to enter the inner pores and fully contact the catalyst. The mesopores on the pore wall can also provide more active sites for gas-solid contact.
[0145] Test Example 2: This test example provides the performance test results of the macroporous and mesoporous ternary perovskite catalysts of the above embodiments.
[0146] (1) NOx catalytic activity test
[0147] according to Fig.12 The catalytic performance of the porous ternary metal oxides of Example 1, Example 2, Example 5 and Example 6 was tested by the method.
[0148] Fig.25 The catalytic performance of the porous ternary metal oxides of Example 1, Example 2, Example 5, Example 6 and Comparative Example 2 was tested. Fig.25 It can be seen that at 250°C, the order of NO oxidation activity exhibited by each sample is: Example 2> Example 1> Example 6> Example 5> Comparative Example 2. After adding F127 or P123, the formation of mesopores on the pore walls of the macropores can be promoted, the contact between the reaction gas and the catalyst is increased, and the NO conversion rate is further improved. Further comparison shows that the performance of adding F127 (Example 1 and Example 2) is better than the performance of adding P123 (Example 5 and Example 6). Table 7 is the specific surface area data of the above catalysts. It can be seen from Table 7 that, in comparison, the specific surface area of the catalyst with the addition of F127 is greater than the specific surface area of the catalyst with the addition of P123. The specific surface area size is consistent with the catalytic activity ranking, which is Example 2> Example 1> Example 6> Example 5> Comparative Example 2. The above results show that the introduction of mesopores can increase the specific surface area of the catalyst and promote the contact between the catalyst and the reaction gas from a physical level; from a chemical level, it can promote the formation of more oxygen vacancies and produce more active oxygen. Compared with other oxygen atoms, these active oxygen species are more likely to combine with NO to generate NO2, which is conducive to the NO oxidation reaction.
[0149] Table 7 Specific surface area of each catalyst
[0150]
[0151]
[0152] (2) Soot combustion catalytic oxidation test
[0153] The catalytic performance of the porous perovskite catalyst for the catalytic oxidation reaction of soot combustion was evaluated under a gradient temperature increase of 5 vol% O2 and 2000 ppm NO.
[0154] The evaluation method is as follows: the catalyst activity is tested in a fixed bed reactor with a diameter of 30 mm and a length of 500 mm. Weigh 0.1 g of sample and 0.01 g of soot (at a ratio of 10:1), grind them thoroughly in a loose contact manner and put them into a quartz tube. Inject a mixed gas containing 20 mL / min nitric oxide, 5 mL / min oxygen and 25 mL / min nitrogen into the gas channel, inject the sample every 5 minutes, and analyze the composition by gas chromatography; heat from 30°C to 150°C at a heating rate of 10°C / min, and then heat to 600°C at 2°C / min.
[0155] The results of the soot combustion catalytic oxidation test are summarized in Table 8 and Fig.26 .
[0156] Table 8
[0157] Experiment No. <![CDATA[T 10 (℃)]]> <![CDATA[T 50 (℃)]]> <![CDATA[T 90 (℃)]]> Example 1 300.6 380.2 420.3 Example 2 293.8 374.7 416.3 Example 5 319.3 391.1 420.3 Example 6 313.8 384.3 425.7 Comparative Example 2 320.9 397.0 443.5
[0158] From Table 8 and Fig.26 It can be seen that the soot conversion activity (T 50 The order of the size of the catalysts is: Example 2 > Example 1 > Example 6 > Example 5 > Comparative Example 2, which is basically consistent with the results of NO catalytic oxidation activity. Among all the porous perovskite catalysts, the sample of Example 2, which showed the best activity, had a T 10 , T 50 , T 90 are 293.8°C, 374.7°C and 416.3°C respectively. The T 50 Compared with the T 50 The temperature of the catalyst was lowered by about 22°C. Since NO can be oxidized to NO2, which has stronger oxidation performance than O2, the introduction of NO can improve the soot conversion rate. With the introduction of mesopores, soot can be transported to each macropore and mesopore through the pore wall, making the soot more dispersed, improving the contact between the catalyst and the soot, and facilitating the catalytic oxidation reaction of soot combustion, and further improving the performance of soot combustion. At the same time, the introduction of mesopores can not only induce the generation of more oxygen vacancies, but also induce the activation of adsorbed oxygen into peroxides (O2 2- ), peroxide has stronger oxidizing properties, promoting carbon smoke and active oxygen (O2 2-) combine to form a surface oxygen complex, which is further decomposed into CO2. Therefore, after the introduction of mesopores, the soot combustion performance is further improved.
[0159] (3) Catalyst stability test
[0160] 1. NO catalytic oxidation
[0161] The porous perovskite catalyst of Comparative Example 2 was tested for catalytic stability. The test method was to test the catalyst activity in a fixed bed reactor with a diameter of 30 mm and a length of 500 mm. Weigh 0.1 g of the sample and put it into a quartz tube. Inject 40 mL / min of nitrogen into the infrared chromatographic gas cell in front of the reaction to eliminate other gases inside. After sweeping the background, inject 5 mL / min of nitric oxide as a pollutant and 2.8 mL / min of oxygen; heat from 50°C to 100°C at a heating rate of 10°C / min, and then heat to 250°C at 2°C / min, and keep the temperature constant for measurement. The test results are as follows: Fig. 27 shown.
[0162] from Fig. 27 It can be seen that the porous perovskite catalyst of Comparative Example 2 can maintain a NO conversion rate of about 53% at 250° C. for up to 40 hours.
[0163] The above experiment was carried out on the macroporous and mesoporous ternary perovskite catalyst of Example 2, and the experimental parameters remained unchanged. Fig. 27 It can be seen that the macroporous mesoporous perovskite catalyst of Example 2 can maintain a conversion rate of more than 58% at 250°C for 40 hours, and there is basically no loss in NO conversion rate. It can be considered that after adding the mesoporous structure, the catalyst stability is not affected, and the stability still has a relatively good effect; and the NO conversion rate of the catalyst of Example 2 is further improved compared with the catalyst of Comparative Example 2, indicating that the introduction of mesopores can effectively improve the catalytic activity.
[0164] 2. Carbon smoke combustion
[0165] The catalyst activity was tested in a fixed bed reactor with a diameter of 30 mm and a length of 500 mm. Weigh 0.1 g of sample and 0.01 g of soot (in a ratio of 10:1), grind them thoroughly in a loose contact manner and put them into a quartz tube. A mixed gas containing 20 mL / min nitric oxide, 5 mL / min oxygen and 25 mL / min nitrogen was injected into the gas channel, sampled once every 5 minutes, and the composition was analyzed by gas chromatography; heated from 30°C to 150°C at a heating rate of 10°C / min, and then heated to 600°C at 2°C / min. After each test, the catalyst and soot were remixed and the next cycle test was carried out according to the above method, and at least 5 cycles were tested.
[0166] Fig.28 and Fig.29 The cyclic stability test results of the soot combustion of the catalysts of Comparative Example 2 and Example 2 are shown respectively. After five cyclic stability tests, the obtained cyclic curves are basically the same, and the performance is basically unchanged. 50 The temperature of the catalysts was maintained at about 400°C and 380°C respectively, which indicated that the two catalysts had good stability. 50 The lower temperature indicates that the introduction of mesoporous structure can improve the catalytic performance of soot combustion.
[0167] The above results prove that, in the present invention, after adding a mesoporous structure to a macroporous material catalyst, the stability of the catalyst does not change, and the macroporous mesoporous perovskite catalyst obtained thereby has a higher catalytic stability.
Claims
1. A method for preparing a porous metal oxide, the method comprising: A metal precursor, a block copolymer and a solvent are mixed to obtain a raw material mixed solution, a microsphere template is fully immersed in the raw material mixed solution, and calcined step by step to obtain the porous metal oxide; The metal precursor comprises a lanthanum source, a manganese source and an iron source, and the molar ratio of the lanthanum source to the mass of the block copolymer is 10 mmol:0.5-6 g.
2. The preparation method according to claim 1, wherein The molar ratio of the manganese source to the lanthanum source is less than or equal to 1:1, and the molar ratio of the iron source to the lanthanum source is less than or equal to 1:
1.
3. The preparation method according to claim 1, wherein The block copolymers include P123 and / or F127.
4. The preparation method according to claim 1, wherein The solvent includes methanol and ethylene glycol; Preferably, the volume ratio of methanol to ethylene glycol is 1:1-5.
5. The preparation method according to claim 1, wherein The mass ratio of the lanthanum source to the microsphere template is 1:1-5.
6. The preparation method according to claim 1, wherein The particle size of the microsphere template is 250-400nm.
7. The preparation method according to claim 1, wherein The microsphere template agent includes polymethyl methacrylate microspheres; Preferably, the preparation method of the polymethyl methacrylate microspheres comprises: mixing methyl methacrylate with an initiator in a protective atmosphere, and performing a polymerization reaction to obtain the polymethyl methacrylate microspheres; Preferably, the initiator comprises potassium persulfate; Preferably, the polymerization reaction temperature is 75-85° C., and the polymerization reaction time is 1-2 h.
8. The preparation method according to claim 1, wherein The stepwise calcination includes a first calcination and a second calcination; The temperature of the first calcination is 300-400°C, and the time of the first calcination is 2-4h; The temperature of the second calcination is 550-700° C., and the time of the second calcination is 2-4 hours.
9. A porous metal oxide obtained by the preparation method according to any one of claims 1 to 8; Preferably, the porous metal oxide has macropores and mesopores, and the pore size of the macropores is 200-300 nm; More preferably, the pore size of the mesopores is 2nm-10nm.
10. A catalyst comprising the porous metal oxide according to claim 9, or made of the porous metal oxide according to claim 9; Preferably, the catalyst is a soot oxidation catalyst or a NO x Oxidation catalyst.